2005
DOI: 10.1002/pds.1122
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of prescription of four major antipsychotics: a retrospective study based on medical records of psychiatric inpatients

Abstract: Haloperidol was prescribed to a minority and targeted male patients hospitalized under constraint, using high dosages. Type and rate of co-prescriptions varied considerably between haloperidol and atypicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…This is not the case for other SGAs that clearly have a higher predilection for all drug-induced movement disorders than clozapine. There are several problems, with many of the incidence studies involving SGAs showing dramatic decreases and others showing similar rates including the use of relatively short-term study durations and hence drug exposures, comparisons with high-dose haloperidol treatment as the "gold standard", and the fact that most patients were previously exposed to, or continue to be treated with, firstgeneration agents [2,42].…”
Section: Is Td Disappearing?mentioning
confidence: 99%
“…This is not the case for other SGAs that clearly have a higher predilection for all drug-induced movement disorders than clozapine. There are several problems, with many of the incidence studies involving SGAs showing dramatic decreases and others showing similar rates including the use of relatively short-term study durations and hence drug exposures, comparisons with high-dose haloperidol treatment as the "gold standard", and the fact that most patients were previously exposed to, or continue to be treated with, firstgeneration agents [2,42].…”
Section: Is Td Disappearing?mentioning
confidence: 99%
“…Relevance to current prescription pattern These data, dating from a period where atypical antipsychotic prescription had not reached its present levels, 28,29 are still relevant today. First, demographical and clinical factors should be stable across time, as no dramatic change occurred in the mental health system, and this study provides valuable information on how (if at all) these factors influence prescription patterns.…”
Section: Inertia or High Prevalence Of Chemo-resistance?mentioning
confidence: 99%
“…Furthermore, it has been shown that atypical anti-psychotics have a strong impact on doses (standard or low doses more frequently prescribed compared to typical anti-psychotics). 28 Therefore, the tendency observed of higher dosage for typical and lower dosage for atypical anti-psychotics is probably still true and even accelerating. Another result requiring confirmation is the seemingly increasing weight of atypical anti-psychotics in anti-psychotic combinations (coefficient increasing from 0.30 to 0.45 between 1993 and 1999).…”
Section: Inertia or High Prevalence Of Chemo-resistance?mentioning
confidence: 99%
“…Due to the high prevalence of depressive disorder, the antidepressant drugs have become one of the most common medications in western countries, with as an example of 6% of users in France [19]. However, only a small proportion of MDD patients receive adequate treatment, with only one third reported a complete remission after trial of a first antidepressant followed by progressively lower response rates with each subsequent antidepressant trial [20].…”
Section: Introductionmentioning
confidence: 99%